Analisis Trianggulasi Antar-reporter Terhadap Persepsi Pendidikan Dasar dan Penanggung Jawab Pendidikan - Herien Puspitawati (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2010)
Abstract: The purpose of this crosssectional research was to describe similiarity and   difference betwen parents,  principals, and school comitee towards perception of basic education and educational fund provider. The collected data was secondary data, i.e. 400 parents from 16 elementary schools and 24 junior high schools. The data was analyzed by  descriptive  and structural equation modelling (SEM).  Results showed: there is a positive correlation inter-reporter   towards similiarity of basic education perception and educational fund provider between  principals and school comitee;   there is a negative correlation inter-reporter   towards difference of basic education perception and educational fund provider between  principals, parents, and school comitee;  there is a positive correlation inter-reporter   towards similiarity of basic education perception and educational fund provider between  principals, parents and school comitee.